Analisis Kolaborasi Divisi Sumber Daya Manusia dan Pemasaran dalam Membangun Keunggulan Kompetitif - Anisa Desta Syafitri; Munawaroh Munawaroh (Pusat Riset dan Inovasi Nasional, 2025)
Collaboration between Human Resources (HR) and Marketing divisions strategically builds competitive advantage amidst increasingly complex market competition. The Human Resources (HR) division manages human resources as the company's main asset, while the Marketing division focuses on strategies to meet market needs and strengthen customer relationships. When these two divisions work collaboratively, they can create significant added value for the organization. The success of the collaboration depends on several factors, such as effective communication, a work culture that supports cross-divisional collaboration, and the use of technology to support data-based decision-making. The main challenges in this collaboration include differences in operational objectives between the Human Resources (HR) and Marketing divisions, lack of coordination, and obstacles in aligning strategic priorities. However, these challenges can be overcome with a structured approach to create optimal synergy.